MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 4–5 TAHUN MELALUI MEDIA BIG BOOK DI KB PERMATA IBU KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Azriha, Azriha; Isjoni, Isjoni; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in the ability to speak in children aged 4-5 years through the media big book in play group Permata Ibu District of Koto Kampar Hulu regency of Kampar . This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years who are 20 children on KB Permata Ibu. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis and quantitative. The research showed that the big media book can improve the ability to speak in children aged 4-5 years. It can be seen from the increase in the average percentage of the ability to speak in the first cycle of 42.6% which is the criterion begins to develop (MB) and an increase of 50% in the second cycle to 64.8% which are in developing appropriate criteria expectations (BSH). So, the big media book can improve speaking skills of children aged 4-5 years in group Permata Ibu District of Koto Kampar Hulu regency of KamparKeywords : Speech, Media Big Book